Sustainable and inclusive development of finfish mariculture in Cambodia: Perceived barriers to engagement and expansion. (February 2023) - Larson, Silva; Hoy, Sreynov; Thay, Somony; Rimmer, Michael A.
Abstract: Finfish mariculture, dominated by production of Asian seabass ( Lates calcarifer ), is of high economic importance in Cambodia and is providing substantial benefits to engaged communities in coastal areas. Using semi-structured face-to-face interviews, we explore perceived barriers to engagement in the industry in three coastal districts of Cambodia where such farming is undertaken. We explore obstacles faced by current finfish mariculture value chain actors, eliciting perceptions of 56 female and male current participants. We also elicit perceptions of the industry entry restrictions by interviewing 62 men and women in the same communities, but who are currently not engaged in finfish mariculture. Specifically including men, women, youths and religion in the study sample, we also tested for potential differences in perceptions of the barriers based on demographic characteristics. The most pertinent areas for strengthening the value chain were identified by participants as: Strengthening training and technical support services; Improving availability of good quality fingerlings; Promoting compounded feeds to replace 'trash' fish; and Supporting value chain inclusivity, development and diversification. The most common obstacles to entry into the industry were reported as lack of: Finance and financial support; Security of access to land and water; Technical support services and experience; and Time and available labour. Barriers and participant needs identified in this study indicate a set of emerging priorities for both the Cambodian Fisheries Administration and the international donor community. Highlights: Finfish mariculture provides substantial benefits to coastal areas in Cambodia. We report on industry perceptions of 118 women, men and youth. Training, fingerlings, feed and market diversification key barriers for growth. Lack of finance and labour, and security of access identified as barriers to entry. Emerging priorities for government and donors proposed.